Estradiol Alters the Virulence Traits of Uropathogenic Escherichia coli - Engelsöy, Ulrik; Svensson, Maria A.; Demirel, Isak (Frontiers in Microbiology, 2021)
Uropathogenic E. coli (UPEC) is the most common bacteria to cause urinary tract infection (UTI). Post-menopausal women have an increased risk of recurrent UTI. This is partly explained by estrogenic effects on host defenses against UTI. Current research is mostly focused on how UPEC affects host factors, but not so much is known about how host factors like hormones affect UPEC virulence. The aim of the present study was to investigate the impact of estradiol exposure on the virulence of UPEC. We found that a post-menopausal concentration of estradiol increased CFT073 growth and biofilm formation, but not the pre-menopausal concentrations. Real time-qPCR showed that estradiol altered the expression of genes associated with the iron acquisition system and metabolic pathways in CFT073. We also found that estradiol in a dose-dependent manner increased the expression of fimH and papC adhesins and increased colonization and invasion of bladder epithelial cells. The pre-menopausal concentration of estradiol also suppressed cytokine release from bladder epithelial cells. Additionally, we also showed, using a C. elegans killing assay that estradiol increased the survival of CFT073 infected C. elegans worms. Taken together, our findings show that estradiol has the ability to alter the virulence traits of UPEC.